EFFECT OF WHEAT SEED SIZE AND SOWING DEPTH ON GERMINATION AND SOME SEEDLING CHARACTERISTICS - Mohamed A . Al-Noori (Mesopotamia Journal of Agriculture)
Experiment were carried out in field crops experiment location in 2006-2007 to investigate the effect of seed size and sowing depth on germination and seedling characters . Wheat seeds of Sham-6 variety were separated by size ( small , Medium , and large ) using standard sieves no. 7 and no. 8 . The seeds passed through sieve no.8 (2.36 mm) were small , while those passed through sieve no. 7 (2.83 mm) were medium , the seed retained on sieve no.7 were large . Seeds sown at 2 , 4 and 6 cm depth in plastic pots filled with loamy soil . The results demonstrate a significant predominance of large seeds in percentage and speed of germination , seedling elongation velocity , fresh and dry weight of seedlings and roots , tall of the longest root and the percentage of consumed food reserve in seeds . There is a significant decrease in no. of days to complement germination and occurrence of second leaf in 50 % seedling , there are markedly similarity between large and medium seeds . The seedling grown from 2 and 4 cm depths were predominance in most characters comparing with that grown from 6 cm depth . The interaction were significant in most characters , the general trend were the mastery of large seeds in lower depth in most characteristics , simple correlation coefficient was determined between all characters . This trail shows obvious differences in growth due to variation in seed size and sowing depth , so raising in seed size uniformity may achieve uniform growth which will reflect on final yield .